009 Predicting infection risk in multiple sclerosis patients treated with ocrelizumab: a retrospective cohort study. (23rd August 2021) - Seery, Nabil; Sharmin, Sifat; Li, Vivien; Nguyen, Ai-Lan; Meaton, Claire; Atvars, Roberts; Taylor, Nicola; Tunnell, Kelsey; Carey, Joh; Marriott, Mark P; Buzzard, Katherine A; Ross, Izanne; et al.
Abstract : Objective: To examine factors determining risk of self-reported infections and antimicrobial use in patients receiving Ocrelizumab for MS. Methods: Retrospective, observational cohort study conducted in Ocrelizumab-treated patients at the Royal Melbourne Hospital. The association of clinical and laboratory factors with self-reported infection rate and antimicrobial use were estimated using univariate and multivariable logistic regression models. Results: 185 patients were included in the study, and 176 infections were reported in 89 patients (46.1%), and in 47 patients (25.3%) antimicrobial use was identified. In univariate analyses, a higher serum IgA was associated with reduced odds of infection (OR 0.44, 95% CI 0.25 - 0.76). In multivariable analyses, older age (OR 0.94, 95% CI 0.88 - 0.99), higher serum IgA (OR 0.37, 95% CI 0.17 - 0.80) and higher serum IgG (OR 0.81, 95% CI 0.67 - 0.99) were associated with reduced odds of infection. Older age (OR 0.85, 95% CI 0.75 - 0.96) and higher serum IgA (OR 0.23, 95% CI 0.07 - 0.79) were associated with reduced odds of antimicrobial use, whilst longer MS disease duration (OR 1.22, 95% CI 1.06 - 1.41) and higher EDSS (OR 1.99, 95% CI 1.02 - 3.86) were associated with increased odds of antimicrobial use. Conclusions: Higher serum IgA, IgG and older age were associated with reduced odds of infection. Our findings highlight non-uniformity of infection risk in Ocrelizumab-treated MS patients, and substantiate the need to monitor immunoglobulin levels pre-treatment and whilst on therapy.